2003
DOI: 10.1097/01.tp.0000061770.39569.7f
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppression with FTY720 and cyclosporine A inhibits rejection of adult porcine islet xenografts in rats

Abstract: Immunosuppression with FTY720 plus CsA inhibited almost all morphological signs of pig-to-rat islet xenograft rejection for up to 24 days after transplantation. Diabetic rats transplanted with APIs and immunosuppressed with FTY720 plus CsA remained normoglycemic for 53.0+/-15.8 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
1
21
0
1
Order By: Relevance
“…In the past year, there have been numerous reports of the therapeutic potential of this compound in the context of autoimmune disorders and transplantation. FTY-720 appears to be a powerful immunosuppressant that, when used in combination with cyclosporine, abrogates xenograft rejection in several systems Koshiba et al, 2003;Maeda et al, 2003]. The protective effect is thought to be due to a decrease in lymphocyte infiltration into the xenograft site.…”
Section: Lysophospholipids and The Immune Systemmentioning
confidence: 92%
“…In the past year, there have been numerous reports of the therapeutic potential of this compound in the context of autoimmune disorders and transplantation. FTY-720 appears to be a powerful immunosuppressant that, when used in combination with cyclosporine, abrogates xenograft rejection in several systems Koshiba et al, 2003;Maeda et al, 2003]. The protective effect is thought to be due to a decrease in lymphocyte infiltration into the xenograft site.…”
Section: Lysophospholipids and The Immune Systemmentioning
confidence: 92%
“…They found that this combination inhibited almost all morphological signs of pig-to-rat islet xenograft rejection for up to 24 days after transplantation (30) . Fotiadis et al (13) used mycophenolatemofetil (MMF) and CsA to check the positive or adverse effects of MMF as a single agent.…”
Section: Discussionmentioning
confidence: 99%
“…We report that, although treatment with FTY720 alone does not influence graft survival in other xenogenic transplantation models (32)(33)(34)(35)43), it significantly delays the rejection of rat-to-mouse xenogenic concordant corneal transplants.…”
mentioning
confidence: 92%
“…It inhibits lymphocyte emigration from the peripheral lymphoid organs and thymus (32)(33)(34)(35)(36), dramatically reducing the number of lymphocytes, especially T cells in the circulation (32,36,37), grafts (37,38) and tissues (30,39,40). Sequestration of lymphocytes in lymph nodes and Peyer's patches (41)-although less pronounced in mice (42)-is believed to be the dominant mode of action of FTY720, although long-term treatment also reduces the proliferative response of mouse lymphnode-derived T cells to alloantigens (42).…”
mentioning
confidence: 99%